Application of Distance Learning at Technical Universities - S. A. Kras’ko; L. G. Sergeeva; N. N. Mikhailova (Высшее образование в России)
The article focuses on the application of distance learning in training students at higher education institutions. The main features of the educational process in the system of distance learning are the following: flexibility, modular structure, specialized quality control tools, communication tools, differentiated teaching, special learning tools, and didactic means. Nevertheless, there are certain problems related to students’ motivation, self-organization and time-management. The authors dwell on the details of the application of this form of training in the work with correspondence students and distance learning students at technical university. The faculty of the Department of the General, Analytical and Applied Chemistry of Ufa State Petroleum Technological University is actively implementing distance learning both for fulltime and correspondence students. Based on the Moodle platform, the authors have worked out the electronic courses of chemical disciplines. The article considers their main blocks such as: instructive, communicative, informational (theoretical and practical parts) and final control. Laboratory classes are an essential part of learning chemical disciplines, and since correspondence students cannot master their practical skills at chemistry laboratory classes, there are special video lections with the experiments recorded. The experience in organization of distance learning for correspondence students shows that an active self-reliant work together with the feedback from a teacher is a good way to become a competent and creative specialist. The article proves the perspective of using distance learning in teaching students of various forms of education.